Optimization of injection molding parameters for WC-TaC-6Co - Prathabrao, M.; Amin, S.Y.M.; Othman, M.H.; Shahbudin, S.N.A. (Science Publishing Corporation, 2019)
The main purpose of this paper is to optimize the injection moulding parameters of WC-Co with TaC as Grain Growth Inhibitor (GGI), through Design of Experiment – Taguchi Method. The selected responses that need to be controlled are shrinkage and warpage. The parameters that were taken into considerations were GGI percentage, injection temperature, injection pressure and injection speed. In this study, L9 (34) orthogonal array from Taguchi Method was chosen as experimental setup and the responses were analyzed using Minitab version 16. Best parameters combinations chosen are, GGI (0.8 wt. % and 1.2 wt. %), injection temperature (145°C), injection pressure (45% and 55%) and injection speed (40%) for minimal shrinkage and warpage. Based on these findings, it is concluded that by controlling the optimum parameter setting, best quality of desired product can be easily achieved and maintained throughout the process.